Social entrepreneurship in the selected neo-Pentecostal churches: A holistic salvation - Mookgo S. Kgatle; Semape J. Manyaka-Boshielo (Verbum et Ecclesia, 2023)
Pentecostalism is a Christian tradition known for personal salvation, baptism in the Holy Spirit, the gifts of the Holy Spirit, divine healing and personal encounter with God through the work of the Holy Spirit. However, Pentecostalism is not limited to these; the tradition also ministers the full gospel that affects a holistic person, meaning body, soul and spirit. This article demonstrated that the holistic salvation approach is a motivation for social entrepreneurial activities in the selected neo-Pentecostal churches in South Africa. The article worked within the social entrepreneurial framework to argue that the neo-Pentecostal churches minister to their followers holistically. Pentecostalism transforms people’s lives in daily living, particularly the poorest of the poor communities through entrepreneurial orientation. The researchers’ methodology was a case study approach of four neo-Pentecostal churches in South Africa that have shown social entrepreneurship factors. In addition, the participant observation method was used in highlighting entrepreneurial activities in these churches.